Ammoniacal nitrogen recovery from pig slurry using a novel hydrophobic/hydrophilic selective membrane. Issue 5 (October 2022) - Serra-Toro, Andreu; Astals, Sergi; Madurga, Sergio; Mata-Álvarez, Joan; Mas, Francesc; Dosta, Joan
Abstract: The implementation of the circular economy paradigm in intensive pig farming requires technologies able to recover ammoniacal nitrogen from pig slurries. This research explores the feasibility of a novel hydrophobic/hydrophilic non-porous membrane to recover ammoniacal nitrogen from pig slurry at ambient temperature and using a H2 SO4 solution as trapping agent. The influence of (i) the pH of the feed solution, (ii) the volume ratio between feed and trapping solution, and (iii) the trapping solution concentration on nitrogen recovery and flux were evaluated using a synthetic solution and pig slurry. The best performance was achieved when the pH of the feed solution was controlled at 9.0, where average fluxes of 145 and 116 g N/(m 2 ·day) were achieved for the synthetic solution and pig slurry after 24 h, respectively. Decreasing the feed-to-trapping volume ratio improved the recovery efficiency after 24 h from 62% to 74% for the synthetic solution and from 32% to 46% for pig slurry. However, renewing the H2 SO4 concentration of the trapping solution only led to minor improvements despite the higher reagent consumption. The diffusion coefficients of NH3 and NH4 + through the membrane at pH 9.0 were (7.3 ± 0.2)·10 –11 and (2.1 ± 0.1)·10 –11 m 2 /s for the synthetic solution and (2.7 ± 0.1)·10 –11 and (1.0 ± 0.1)·10 –11 m 2 /s for the pig slurry, respectively. The capacity of ions to diffuse through the membrane is a distinctive feature of this membrane and allowed recovering 33% of potassium and 21% of phosphate in pig slurry after 24 h. Graphical Abstract: ga1 Highlights: The performance of a novel ammonia selective membrane was evaluated. The highest nitrogen flux was obtained when the pH of the feed solution was 9.0. For pig slurry, 46% and 59% of the nitrogen was recovered in 24 and 48 h. A trapping solution concentrated in NPK and free of heavy metals was obtained. A model was used to calculate NH3 and NH4 + diffusion coefficients at each condition.